Phytocompounds vs. Dental Plaque Bacteria: In vitro Effects of Myrtle and Pomegranate Polyphenolic Extracts Against Single-Species and Multispecies Oral Biofilms - Sateriale, Daniela; Imperatore, Roberta; Colicchio, Roberta; Pagliuca, Chiara; Varricchio, Ettore; Volpe, Maria Grazia; Salvatore, Paola; Paolucci, Marina; Pagliarulo, Caterina (Frontiers in Microbiology, 2020)
In the last decades, resistant microbial infections rate is dramatically increased, especially infections due to biofilm producing strains that require increasingly complex treatments, and are responsible of rised mortality percentages than the other infectious diseases. Biofilm formation represents a key virulence factor for a wide range of microorganisms that cause chronic infections, and considering the multifactorial nature of biofilm development and the related drug tolerance, the treatment of biofilm-causing bacteria infections represents a great challenges for the. Among new alternative strategies to conventional antimicrobial agents, the scientific interest has shifted to the study of biologically active compounds from plant-related extracts with known antimicrobial properties, in order to evaluate also their anti-biofilm activity. In this frame, the aim of this study has been to define the antibiofilm profile of polyphenolic extracts from myrtle leaf and pomegranate peel against oral pathogens of dental plaque, an excellent poly-microbial biofilm model. In particular, the in vitro anti-biofilm properties of myrtle and pomegranate extracts, also in binary combination, were highlighted. In addition to inhibiting the biofilm formation, the tested polyphenolic extracts have been proved to destroy both pre-formed single and multi-species biofilms formed by Streptococcus mutans, Streptococcus oralis, Streptococcus mitis and Rothia dentocariosa oral isolates, suggesting that the new natural sources are rich of promising compounds able to counteract biofilm-related infections.